Note on the discovery of Carboniferous amber associated with the seed fern Linopteris obliqua, Sydney Coalfield, Nova Scotia, Canada - Mastalerz, Maria; Zodrow, Erwin L. (Atlantic Geoscience, 2022)
We report on a discovery of amber from the Carboniferous sedimentary rocks of the Sydney Coalfield, Nova Scotia, Canada. The amber occurs in the form of droplets and as a linear feature and ranges in colour from light brown to dark purple. The amber was found in situ in siltstone above the Middle Pennsylvanian Hub coal seam, where it was associated with abundantly abscised pinnules of the seed fern Linopteris obliqua. The amber specimens were analyzed by infrared spectrometry and their spectrochemical characteristics were compared with those of other fossil ambers. This discovery not only expands the inventory of amber to as old as 300 million years, but also documents that Carboniferous seed ferns were able to utilize biosynthetic mechanisms to produce resinous exudates.